2021
DOI: 10.32473/jfmca.v67i1.127635
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Combined Nozzle Orientation and Truck Speed on Efficacy of Ultra-Low-Volume Spray Against Caged Aedes Albopictus in Urban Gainesville, Florida

Abstract: A field study was conducted to evaluate the combined effect of nozzle orientation and vehicle travel speed on droplet dispersion and mosquito mortality of an adulticide applied from a truck mounted ULV sprayer in the City of Gainesville, Florida. Three multi-block areas with dense, medium, and sparse vegetation were selected for the study. Aqua-Reslin ® was applied in each area in the following treatment combinations: a) horizontal nozzle at 24 km/h travel speed, b) 45° upward orientation (standard) at 16 km/h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
1
1
Order By: Relevance
“…In this study, we found that spray from the horizontal (0°) nozzle orientation showed greater mortality near the spray line, but resulted in less mortality at farther distances when compared to the 22° and 45° orientations. This result generally contradicts to what has been observed in prior studies (Farooq et al 2017 andJiang et al 2020) which showed higher mortality from horizontal nozzle at all distances. A key difference in our study was that the application site (while in an open field) was surrounded by forest on three sides (Figure 1).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this study, we found that spray from the horizontal (0°) nozzle orientation showed greater mortality near the spray line, but resulted in less mortality at farther distances when compared to the 22° and 45° orientations. This result generally contradicts to what has been observed in prior studies (Farooq et al 2017 andJiang et al 2020) which showed higher mortality from horizontal nozzle at all distances. A key difference in our study was that the application site (while in an open field) was surrounded by forest on three sides (Figure 1).…”
Section: Discussioncontrasting
confidence: 99%
“…aegypti and Ae. albopictus (Skuse) (Jiang and Farooq 2016;Jiang et al 2020). During these studies, effectiveness of spray was checked at 1.5 m above the ground.…”
Section: Introductionmentioning
confidence: 99%